Development of the Hypogonadism Impact of Symptoms Questionnaire Short Form: Qualitative Research. Issue 11 (1st November 2016) - Gelhorn, Heather L.; Bodhani, Amit R.; Wahala, Louisa S.; Sexton, Chris; Landrian, Amanda; Miller, Michael G.; Derogatis, Leonard; Dobs, Adrian; Revicki, Dennis A.
ABSTRACT: Introduction: Hypogonadism in men is often associated with poor libido, erectile dysfunction, irritability, fatigue, and psychological and relationship problems. Many of these symptoms can be best assessed through patient report. The 28-item Hypogonadism Impact of Symptoms Questionnaire (HIS-Q) was developed to evaluate hypogonadism symptoms in men with low testosterone in the context of clinical trials. Aim: To develop a briefer version of the HIS-Q that could be practical for use in treatment settings. Methods: Participants with low testosterone levels and symptoms consistent with hypogonadism were recruited through clinical sites. Focus groups and interviews were conducted to elicit symptom concepts and identify those that were most relevant to patients, including changes as a consequence of treatment. Main Outcome Measures: Systematic analysis of the qualitative data and expert clinician input were used to develop the HIS-Q short form (HIS-Q-SF). One-on-one cognitive interviews were conducted to confirm the content validity of the HIS-Q-SF. Results: Thirty-five men participated in this qualitative research. Concept elicitation was conducted through focus group discussions (n = 18) and telephone interviews (n = 2); then, the draft HIS-Q-SF was evaluated through cognitive interviews (n = 15). The mean age of total sample was 53.2 ± 6.8 years, and the mean serum total testosterone level was 184.9 ± 55.2 ng/dL. Results suggest that the HIS-Q-SF has demonstrated content validity, including the content coverage, comprehensibility, and the appropriateness of the response options and recall period. The final version of the HIS-Q-SF includes 17 items and is aligned with the original longer version of the instrument. Conclusion: The HIS-Q-SF is a comprehensive measurement of hypogonadism symptom severity in men. Content coverage and content validity were confirmed. The instrument will be evaluated further to establish the psychometric characteristics and to assess the utility of the measurement in clinical treatment settings.